2020
DOI: 10.1186/s12885-020-6614-0
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy could not bring survival benefit to HR-positive, HER2-negative, pT1b-c/N0–1/M0 invasive lobular carcinoma of the breast: a propensity score matching study based on SEER database

Abstract: Background The benefit of adjuvant chemotherapy in invasive lobular carcinoma (ILC) is still unclear. The objective of the current study was to elucidate the effectiveness of adjuvant chemotherapy in hormone receptor (HR)-positive, human epidermal growth factor receptor 2 (HER2)-negative, pT1b-c/N0–1/M0 ILC. Methods Based on Surveillance, Epidemiology, and End-Results (SEER) database, we identified original 12,334 HR-positive, HER2-negative, pT1b-c/N0–1/M0 ILC patients, who were then divided into adjuvant ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…However, the study was difficult to interpret as HER2 status was not known for any of the patients. Subsequently, similar findings have been reported by Marmor et al in ER+HER2− stage I–II ILC and IDC, and by Hu et al who found no difference in overall survival in early-stage ER+HER2− ILC after ACT vs. no chemotherapy [ 16 , 20 ]. In contrast, de Nonneville et al found there was a survival advantage to ACT in high-risk ER+HER2− ILC, defined as having either macroscopic lymph node involvement, or a tumour size over 20 mm and LVI, but not in low-risk ILC [ 43 ], as did Tamirisra et al [ 42 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, the study was difficult to interpret as HER2 status was not known for any of the patients. Subsequently, similar findings have been reported by Marmor et al in ER+HER2− stage I–II ILC and IDC, and by Hu et al who found no difference in overall survival in early-stage ER+HER2− ILC after ACT vs. no chemotherapy [ 16 , 20 ]. In contrast, de Nonneville et al found there was a survival advantage to ACT in high-risk ER+HER2− ILC, defined as having either macroscopic lymph node involvement, or a tumour size over 20 mm and LVI, but not in low-risk ILC [ 43 ], as did Tamirisra et al [ 42 ].…”
Section: Discussionsupporting
confidence: 80%
“…Truin [ 19 ] did compare ER+ ILC to IDC, and observed no considerable difference in survival after treatment with both adjuvant endocrine therapy and ACT between the two histological subtypes. Several other studies have shown that ACT did not improve survival for patients with hormone receptor (HR)-positive, early-stage ILC, when compared to ILC treated with endocrine therapy alone [ 16 , 20 ]. However, these studies did not directly compare overall survival to ER+ IDC, and so it is not clear whether this finding is confined to just ILC, or if it also applies to ER+ IDC of similar stage.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4,24,25 Multiple studies have demonstrated that patients who have ILC are treated less often with CT compared with those who have similar tumor stage and IDC histology, with further studies questioning whether patients who have ILC derive any benefit from the addition of CT to their treatment. 8,9,26,27 The evolving myriad of genomic assays allows for more accurate and personalized patient care. TAILORx and the recently reported results from RxPONDER have joined retrospective analyses of earlier randomized controlled trials in changing practice and establishing the role of the RS in differentiating patients who have ER-positive, HER2-negative, N0 and N1 breast cancer according to their risk of recurrence and potential benefit from CT.…”
Section: Discussionmentioning
confidence: 99%
“…These tendencies may be explained by early trials demonstrating that patients with ILC had no advantage from the addition of CT to their treatment. 8,9,26,27 They may have been further influenced by findings that the RS had no prognostic value in patients with ILC. Christgen et al reported that 5-year disease-free survival in a cohort of 353 patients with ILC was unaffected by the RS in multivariable analysis, findings that were limited because their cohort included only 27 patients with a high RS.…”
Section: Discussionmentioning
confidence: 99%
“…The National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) database covers approximately 28% of the population with cancer in the US. 17 The Korean Breast Cancer Registry (KBCR) is a registry prospectively maintained by the Korean Breast Cancer Society. In 2014, the register included more than 50% of patients with newly diagnosed breast cancer in Korea.…”
Section: Introductionmentioning
confidence: 99%